Broadening the Gene Pool: The Value of the Humanities Future Success - Grillo, Michael (Maine Policy Review, 2015)
Readers are asked, “How can we hope to imagine our future, and more importantly, address what it brings, if we do so using frameworks defined only by our present and most immediate needs?” Art historian Michael Grillo that study of the humanities ensures our best chances of creative thought, cultural growth, and meaningful survival
Keywords: humanities; art history